2012
DOI: 10.1109/tc.2010.267
|View full text |Cite
|
Sign up to set email alerts
|

Space-Efficient TCAM-Based Classification Using Gray Coding

Abstract: Ternary content-addressable memories (TCAMs) are increasingly used for high-speed packet classification. TCAMs compare packet headers against all rules in a classification database in parallel and thus provide high throughput unparalleled by software-based solutions. TCAMs are not well-suited, however, for representing rules that contain range fields. Such rules have to be represented by multiple TCAM entries. The resulting range expansion can dramatically reduce TCAM utilization. The majority of real-life dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(11 citation statements)
references
References 20 publications
(19 reference statements)
0
11
0
Order By: Relevance
“…In comparison, the SRGE algorithm (short range gray encoding) which was proposed in [20] is an efficient, database-independent encoding scheme. This scheme does not require extra bits.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison, the SRGE algorithm (short range gray encoding) which was proposed in [20] is an efficient, database-independent encoding scheme. This scheme does not require extra bits.…”
Section: Related Workmentioning
confidence: 99%
“…This scheme does not require extra bits. Bremler-Barr and Hendler [20,21] proposed SRGE as an independent range encoding algorithm based on their observations. They found that encoding the ranges that are available in queues in real databases would be much more efficient when using the Gray code.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-layout simulations at 45-nm technology disclosed that the power is decreased substantially up to 93%. Many other techniques are presented to improve the performance of the CAM cells [14][15][16][17][18][19][20][21]. But all methods based on CMOS result in high energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The parallel hardware search scheme of the CAM outperforms the software-based search algorithms [1]. Thus, CAM is an important lookup table hardware for applications like network routers [2], data compression [3], image processing [4], and data management [5]. The parallel active circuits in CAM make it power hungry.…”
Section: Introductionmentioning
confidence: 99%